Pengaruh Gaya Hidup Hedonisme dan Kemudahan Penggunaan QRIS Terhadap Perilaku Konsumtif Gen-Z di Kota Denpasar - Meilani, I Gusti Ayu Ratih; Kusuma, Putu Sri Arta Jaya (Accounting Research Unit (ARU Journal), 2024)
The financial sector has reaped significant benefits from today's rapid technology breakthroughs, particularly in the payment system, which is transitioning to a digital non-cash payment system. The aim of this study is to determine how Denpasar City's Gen-Z consumers' behavior is influenced by hedonistic lifestyles and the ease of use of QRIS. This study employs quantitative methodologies. Purposive sampling procedures were used using fifty persons as samples. Data is collected using Google Form questionnaires that employ a Likert scale. The dependent variable in this study is Consumptive Behavior (Y), and the independent factors are Hedonistic Lifestyle (X1) and QRIS Ease of Use (X2). The data was then utilized to perform the partial t test, the simultaneous f test, multiple linear regression analysis, and the normality test.